Morphological alterations in the ovaries of Amblyomma cajennense semi-engorged ticks exposed to ethanolic extract of Acmella oleracea - Anholeto, Luís Adriano [UNESP]; de Oliveira, Patrícia Rosa [UNESP]; Rodrigues, Rodney Alexandre Ferreira; Yamane, Lais Thiemi; Castro, Karina Neoob de Carvalho; Camargo-Mathias, Maria Izabel [UNESP] (Wiley, 2018)
The present study analyzed the effects of different concentrations of Acmella oleracea crude ethanolic extract (EEAO) on the development of germ cells from semi-engorged Amblyomma cajennense females in order to evaluate the potential of this natural chemical as a strategy to control these important ectoparasites. A hundred semi-engorged females were divided into five groups (duplicates) (10 animals/group): Control 1 (distilled water); Control 2 (solvent ethanol 50% and DMSO 1%); and Treatment I to III (3.1, 6.2, and 12.5 mg/mL of EEAO, respectively). For the exposure of the ticks to the extract was used the Adult Immersion Test. After the exposition, the ovaries were removed and submitted to histological analysis using Harris hematoxylin and aqueous eosin. The histochemical tests were performed using PAS and Bromophenol blue staining techniques, for the detection of total polysaccharides and total protein, respectively. The extract caused significant alterations in the oocytes, including changes in the shape of the cells, disorganization, and cytoplasmic vacuolation, decrease in the number of yolk granules and germ vesicle fragmentation. These alterations were more intense in the oocytes in initial developmental stages (I and II). The results obtained in this study confirm the cytotoxic potential of the ethanolic extract of A. oleracea on the germ cells of A. cajennense females, opening up the possibility to use this extract as an alternative to control these ectoparasites.
Keywords: control; jambu; morphology; oocytes; ticks